2015
DOI: 10.1016/j.bbi.2014.12.015
|View full text |Cite|
|
Sign up to set email alerts
|

CXCR4+CD45− BMMNC subpopulation is superior to unfractionated BMMNCs for protection after ischemic stroke in mice

Abstract: Cell-based therapy is considered to be a promising therapeutic strategy for stroke treatment. Although unfractionated bone marrow mononuclear cells (BMMNCs) have been tried in both preclinical and clinical trials, the effective subpopulations need to be identified. In this study, we used fluorescence-activated cell sorting to harvest the CXCR4+CD45+ and CXCR4+CD45− BMMNC subpopulations from transgenic mice that express enhanced green fluorescent protein. We then allogeneically grafted unfractionated BMMNCs or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Among many cell types, bone marrow mononuclear cells (BMMNCs) are particularly attractive for acute ischemic stroke treatment because they are composed of different kinds of stem cells, can be rapidly isolated without cultivation, and can be used in autologous applications [6]. Several research groups have shown that BMMNC transplantation can significantly improve neurologic outcome from ischemic stroke in animal models by cell differentiation [7, 8], secretion of trophic factors [9], and possible immunomodulation [10]. Some phase I/II clinical trials also have shown that BMMNC transplantation can improve clinical outcomes of patients with middle cerebral artery occlusion (MCAO) [1114].…”
Section: Introductionmentioning
confidence: 99%
“…Among many cell types, bone marrow mononuclear cells (BMMNCs) are particularly attractive for acute ischemic stroke treatment because they are composed of different kinds of stem cells, can be rapidly isolated without cultivation, and can be used in autologous applications [6]. Several research groups have shown that BMMNC transplantation can significantly improve neurologic outcome from ischemic stroke in animal models by cell differentiation [7, 8], secretion of trophic factors [9], and possible immunomodulation [10]. Some phase I/II clinical trials also have shown that BMMNC transplantation can improve clinical outcomes of patients with middle cerebral artery occlusion (MCAO) [1114].…”
Section: Introductionmentioning
confidence: 99%
“…Rats were anesthetized with 10 % chloral hydrate (400 mg/kg, intraperitoneally [i.p.]) and then underwent pMCAO with the filament model as described previously [2830]. Only the left MCA was occluded.…”
Section: Methodsmentioning
confidence: 99%
“…mRNA levels of candidate genes were normalized to the endogenous control GAPDH in the same sample. The 2 −ΔΔCt method was used for relative quantification of gene expression as described (Wang et al, 2015a). …”
Section: Methodsmentioning
confidence: 99%